A Study of Self-Care Brands in Pharmacy : Consumer Attitudes in Finland - Ranta, Katri (My University, 2022)
Purpose – The aim of the study is to explore customers' attitudes towards self-care brands in the pharmacy. The investigated brands are classified under two categories either to self-care drugs or self-care non-drugs. The brands are studied according their category. The effect on dependable variable of customer attitude is examined by independent variables of age group, gender, frequency of pharmacy visits and frequency of use. Methodology and Approach – The quantitative study is conducted by online customer survey, which is analysed by using of multiple linear regression analysis. The theoretical background draws on brand image and brand attitudes. The theoretical framework is based on similarly executed empirical studies. Findings – The effect on customer attitudes as dependent variable was examined in respect of different independent variables (age group, gender, frequency of pharmacy visits and frequency of use) to provide information of the studied self-care categories. According to the regression analysis, most of the independent variables explained the dependent variable quite significantly, as at the end of the study, the half of the hypothesized relationships between the independent and dependent variables were approved. Research limitations – The individual brands were examined in respect of their classification. However, the individual brands may have different brand awareness and familiarity among customers, which perspective was not covered by the research. Furthermore, only a limited number of brands were studied, although the study had a large customer sample, but it only corresponded to a small part of the hundreds of self-care brands sold in the Finnish pharmacy market. Practical implications – This study provides marketers with information on customer attitudes toward pharmacy brands when segmenting them into self-care drugs and self-care non-drugs. The intention is to explore if it is advantageous to use this in marketing. Originality – The self-care categorization in pharmacy market is strategically important for the companies for multiple reasons, but is it meaningful to support this from the customer attitude’s point of view.

Tavoite – Tutkimuksen tavoitteena on selvittää asiakkaiden asenteita itsehoitobrändeihin apteekissa. Tutkitut tuotemerkit luokitellaan kahteen kategoriaan joko itsehoitolääkkeisiin tai ei-lääkkeellisiin itsehoitovalmisteisiin, ja brändejä tutkitaan näiden kategorioiden mukaan. Tutkimuksessa tarkastellaan eri riippumattomien muuttujien (ikäryhmä, sukupuoli, apteekkikäyntitiheys ja käyttötiheys) vaikutusta riippuvaan muuttujaan eli asiakkaiden asenteisiin. Menetelmät ja lähestymistapa – Kvantitatiivinen tutkimus tehdään kuluttajaverkkokyselynä, joka analysoidaan käyttämällä multilineaarista regressioanalyysiä. Teoreettinen tausta ammentaa brändikuvasta ja brändiasenteista. Teoreettinen viitekehys perustuu vastaavasti toteutettuihin empiirisiin tutkimuksiin. Havainnot – Vaikutusta asiakkaiden asenteisiin riippuvilla muuttujilla tutkittiin eri riippumattomien muuttujien (ikäryhmä, sukupuoli, apteekkikäyntitiheys ja käyttötiheys) osalta, jotta saadaan tietoa tutkittavista itsehoitokategorioista. Regressioanalyysin mukaan suurin osa riippumattomista muuttujista selitti riippuvan muuttujan varsin merkittävästi, sillä tutkimuksen lopussa puolet hypoteeseista riippumattomien ja riippuvien muuttujien välisistä suhteista hyväksyttiin. Tutkimuksen rajoitukset – Yksittäisiä tuotemerkkejä tarkasteltiin tutkimuksessa niiden luokituksen suhteen. Kuitenkin yksittäisillä brändeillä voi olla erilainen brändituntemus ja -tunnettuus asiakkaiden keskuudessa, mitä näkökulmaa tutkimuksessa ei käsitelty. Lisäksi tutkittiin vain rajoitettu määrä tuotemerkkejä, vaikkakin tutkimuksessa oli suuri otanta vastaajia, se vastasi kuitenkin vain pientä osaa Suomen apteekkimarkkinoilla myydyistä sadoista itsehoitotuotemerkeistä. Käytännön vaikutukset – Tämä tutkimus tarjoaa markkinoijille tietoa asiakkaiden asenteista apteekkibrändejä kohtaan, kun ne jaetaan itsehoitolääkkeisiin ja itsehoitoon kuulumattomiin lääkkeisiin. Tarkoituksena on selvittää, onko tätä hyödyllistä hyödyntää markkinoinnissa. Tutkimuksen merkitys – Apteekin itsehoitobrändien luokittelu on yrityksille strategisesti tärkeää monestakin syystä, mutta onko sitä mielekästä tukea asiakkaiden brändiasenteen näkökulmasta tarkasteltuna.
Keywords: Key words: Brand image, Brand attitude, Self-care, Self-care brand, Pharmacy, Web-survey, Questionnaire, Quantitative study, Linear regression analysis